2010
DOI: 10.1016/j.jhevol.2010.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor anatomy and biomechanics of the Dmanisi hominins

Abstract: The Dmanisi hominins inhabited a northern temperate habitat in the southern Caucasus, approximately 1.8 million years ago. This is the oldest population of hominins known outside of Africa. Understanding the set of anatomical and behavioral traits that equipped this population to exploit their seasonal habitat successfully may shed light on the selection pressures shaping early members of the genus Homo and the ecological strategies that permitted the expansion of their range outside of the African subtropics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 63 publications
7
118
2
1
Order By: Relevance
“…We have previously demonstrated that the same pattern is found for the femur; i.e., A.L. 288-1 and LB1 fall near the human OLS and/or RMA slopes for femoral length on body mass 1/3 (Franciscus and Holliday 1992; Holliday and Franciscus 2009; and see Figure 3a in Pontzer et al 2010). This who was in all likelihood heavier, deviates only -2.2% in humerus length from what would be expected for a recent human of her small body size following an OLS regression model.…”
Section: Resultssupporting
confidence: 64%
“…We have previously demonstrated that the same pattern is found for the femur; i.e., A.L. 288-1 and LB1 fall near the human OLS and/or RMA slopes for femoral length on body mass 1/3 (Franciscus and Holliday 1992; Holliday and Franciscus 2009; and see Figure 3a in Pontzer et al 2010). This who was in all likelihood heavier, deviates only -2.2% in humerus length from what would be expected for a recent human of her small body size following an OLS regression model.…”
Section: Resultssupporting
confidence: 64%
“…Building on earlier ideas (Martin, 1983(Martin, , 1996Aiello and Key, 2002;Aiello and Wells, 2002;Leonard et al, 2003), we showed which of these factors are supported by general relationships that are also found in other mammalian lineages, and argued that special pleading for humans is not needed. These factors include the stabilization of energy intake on a higher level through a change in diet and cognitive and physiological buffering of seasonality effects (van Woerden et al, 2010(van Woerden et al, , 2012 as well as a reduction of energy spent on locomotion through abandonment of climbing and a more efficient bipedalism (Pontzer et al, 2010). The present study suggests that energy subsidies for mothers and infants play a major role in the stabilization of energy intake.…”
Section: Allomaternal Care and Human Evolutionmentioning
confidence: 59%
“…But with more recent finds the curve has tended to smooth out (Schoenemann 2006). The key points appear to be that brain size had already reached 1000 cm 3 one million years ago, that major tooth size reduction in Homo had already happened by 1.7 Ma and that changes to more modern body form came soon afterwards (being achieved by 1.5 Ma as shown by the Nariokotome specimen (Pontzer et al 2010). Certainly, the archaeological record around Lake Turkana shows hominins ranging widely on landscapes that were often semi-arid and offered no prospect of the kind of stable diet of fruits and herbs available to chimpanzees (Bunn and Ezzo 1993;Bunn 1994;Isaac and Behrensmeyer 1997) and much the same can be said for Olduvai (Blumenschine et al 2003).…”
Section: Evidence For Dietary Hypothesesmentioning
confidence: 94%
“…Similar factors would seem to apply to varieties of Homo erectus beyond Africa. Although early Homo from Dmanisi in Georgia retains primitive features at 1.8 Ma, and is relatively small bodied, it had already acquired adaptations for striding locomotion and its toothwear patterns suggest a broadening of diet (Pontzer et al 2010(Pontzer et al , 2011. By this time, it can now be seen, the distribution of early Homo was so wide that it is certain that it must have mastered many environments (Clark 1993: 160) and sleeping in trees could not always have been an option.…”
Section: Dietary Hypothesesmentioning
confidence: 99%